408 Audit - Diagnostic Pathways in Suspected Renal Colic. (19th August 2022) - Siddique, MH; Rauf, M; Klair, A; Mohsin, S; Pearce, S; Ali, D; Anwar, A
Abstract: Introduction: Ureteric colic is common clinical condition but has significant morbidity. Prompt diagnosis and treatment are key to overcome. Therefore, both BAUS and NICE have produced similar guidance which forms the audit standards below Aim: Audit of local practice to national and aspirational guidelines Standards: -A non-contrast CT-KUB should be performed within 14 hours (BAUS) for the standard (non-pregnant adult). -Investigations in all patients should include serum calcium and urate (BAUS). -Non-steroidal anti-inflammatory drugs (NSAIDs) should be given as first-line analgesia (unless contra-indicated) (BAUS / NICE). Intravenous paracetamol should be offered if NSAIDs are contra-indicated or not effective (NICE). Method: Perform a retrospective review of consecutive 705 patients with suspected ureteric colic who had CT-KUB Data collection tool: patient demographics date and time CT-KUB performed positive CT-KUB (i.e., confirming ureteric calculi) serum calcium and urate measured NSAIDs (or other form of analgesia) prescribed (on admission / to take home) Conclusion: 705 patients only 335 patients had CT KUB in 14 hours. Calcium checked was of 305 out 636 patients. Urate being the lowest only 2.6% that's 14 out of 523 patients was checked. Lastly NSAID's 67 patients out of 200 have received it as initial pain management. Summary as follows CT KUB in 14 hours:47% Calcium: 48% Urate: 2.6% NSAID: 33% Recommendations: Make pro-forma called Stone investigations/bundle involving A&E, Radiology and Urology Teaching Present in local audit meeting / departmental teaching sessions (to A&E, radiology, and pharmacy) and discuss areas for improvement Consider outsourcing imaging for CT KUB